Plants with Anti-Ulcer Activity and Mechanism: A Review of Preclinical and Clinical Studies - Prayoga DK; Aulifa DL; Budiman A; Levita J (Dove Medical Press, 2024)
Deshanda Kurniawan Prayoga,1,* Diah Lia Aulifa,2,* Arif Budiman,3,* Jutti Levita4,* 1Master Program in Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 45363, Indonesia; 2Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Padjadjaran University, Sumedang, 45363, Indonesia; 3Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Padjadjaran University, Sumedang, 45363, Indonesia; 4Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, 45363, Indonesia*These authors contributed equally to this workCorrespondence: Jutti Levita, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 46363, Indonesia, Tel +6222-84288888 Ext 3510, Email jutti.levita@unpad.ac.idAbstract: Ulcer disorders including the oral mucosa, large intestine, and stomach mucosa, cause significant global health burdens. Conventional treatments such as non-steroid anti-inflammatory drugs (NSAIDs), proton pump inhibitors (PPIs), histamine H2 receptor antagonists (H2RAs), and cytoprotective agents have drawbacks like mucosal injury, diminish gastric acid secretion, and interact with concurrent medications. Therefore, alternative therapeutic approaches are needed to tackle this health concern. Plants are rich in active metabolites in the bark, roots, leaves, fruits, and seeds, and have been utilized for medicinal purposes since ancient times. The use of herbal therapy is crucial, and regulations are necessary to ensure the quality of products, particularly in randomized studies, to assess their efficacy and safety in treating ulcer disorders. This study aims to explore the anti-ulcer activity of medicinal plants in treating peptic ulcer disease, ulcerative colitis, and aphthous ulcers. Articles were searched in Scopus and PubMed, and filtered for publication from 2013 to 2023, resulting in a total of 460 from Scopus and 239 from PubMed. The articles were further screened by title and abstract and resulted in 55 articles. Natural products, rich in active metabolites, were described to manage ulcer disease by protecting the mucosa, reducing ulcer effects, inhibiting pro-inflammatory factors, and reducing bacterial load, thus improving patients' quality of life. Natural extracts have proven effective in managing other health problems, including ulcers by reducing pain and decreasing lesions. This review provides an overview of preclinical and clinical studies on medicinal plants, focusing on their effectiveness in treating conditions like peptic ulcers, ulcerative colitis, and aphthous ulcers.Keywords: anti-ulcers, aphthous ulcer, botanical drugs, peptic ulcer disease, ulcerative colitis